KONTROVERSI ANAK PAUD MENGIKUTI LES MEMBACA SEBAGAI PERSIAPAN MASUK SEKOLAH DASAR - Fahmi Fahmi (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2017)
Every parents want their child can read early and well before learning in the elementary school but not every child can read early and well because every child have different intelligence and skill. Any others, not every parents aware that their child is not same with child others. to make a try of every parents to teach reading to childrent are different so every child have reading skill are different There are early reading test is as requirement for learning in elementary school. For the children can not read yet so the children can not be delived in the elementary school until the their parents to be worried if their children can not read yet. The teachers and chief of early of children education have been remembered by government and education expert of early of children education that can not do early reading test is as requirement for learning in ele mentary school but until at the moment can be found any elementary school still do it. Reading leaning or reading course is as prepare to learnig in elementary school is make worries the parents and teachers if their children can not read yet. Reading course be hopped can help to improve earling reading skill as requirement for learning in elementary school. Reading course to be be pro and conter of teacher, chief of early of children education, and parents. We all must know that reading course can help to change reading skill in children selves. Big or little change of early reading skill by each skill of child and each parent teach to read hard in the home.